Sex-specific and lasting effects of a single course of antenatal betamethasone treatment on human placental 11β-HSD2. (September 2018) - Braun, F.; Hardt, A.K.; Ehrlich, L.; Sloboda, D.M.; Challis, J.R.G.; Plagemann, A.; Henrich, W.; Braun, T.
Abstract: Introduction: We have previously shown that even a single course of antenatal betamethasone (BET) as an inductor for lung maturity reduces birth weight and head circumference. Moreover, animal studies link BET administration to alterations of the hypothalamic-pituitary-adrenal-gland-axis (HPA). The unhindered development of the fetal HPA axis is dependent on the function and activity of 11β-hydroxysteroiddehydrogenase type 2 (11β-HSD2), a transplacental cortisol barrier. Therefore, we investigated the effects of BET on this transplacental barrier and fetal growth. Methods: Pregnant women treated with a single course of BET between 23 + 5 to 34 + 0 weeks of gestation were compared to gestational-age-matched controls. Placental size and neonatal anthropometrics were taken. Cortisol and ACTH levels were measured in maternal and umbilical cord blood samples. Placental 11β-hydroxysteroiddehydrogenase type 1 (11β-HSD1) protein levels and 11β-HSD2 protein and activity levels were determined. Parameters were analyzed independent of sex, and in subgroups divided by gender and gestational age. Results: In term born females, BET administration was associated with reduced head circumference and decreased 11β-HSD2 protein levels and enzyme activity. Males treated with BET, especially those born prematurely, showed increased 11β-HSD2 protein levels. Conclusion: A single course of BET alters placental glucocorticoid metabolism in a sex-specific manner. Decreased 11β-HSD2 levels in term born females may lead to an increased placental transfer of maternal cortisol and therefore result in a reduced head circumference and a higher risk for altered stress response in adulthood. Further research is needed to conclude the significance of increased 11β-HSD2 levels in males. Highlights: A single course of antenatal BET altered placental glucocorticoid metabolism. Changes were evident several weeks after treatment in term placentas. Placental 11 b-HSD2 protein and activity levels were changed in a sex-specific way. Decreased 11 b-HSD2 levels could result in suppression of the fetal adrenal axis. This could improve adaptation to survive in an adverse environment.